Determinants of Executive Dysfunction: Serum NRF2 and Sociodemographic Profiles in Lombok Island’s Coastal Population - Inayah Wulandari; Nurhidayati Nurhidayati; Ilsa Hunaifi; Arina Windri Rivarti; Herpan Syafii Harahap; Legis Octaviana Saputri; Dini Suryani; Fitriannisa Faradina Zubaidi; Rohadi Muhammad Rosyidi (AKSONA, 2026)
Highlight: Coastal communities show high prevalence of cognitive decline. There is no correlation between NRF2 levels and executive function. Gender and education level were significantly associated with executive dysfunction.   ABSTRACT Introduction: Elderly people frequently suffer from neurodegenerative conditions that affect cognitive function. Redox homeostasis dysregulation plays a significant role in neurodegenerative diseases. Oxidative stress activates the transcription factor called nuclear factor erythroid 2-related factor 2 (NRF2), which is essential for regulating the expression of genes involved in cellular defense mechanisms. Objective: This study aimed to determine the relationship between serum NRF2 levels and executive function, as well as to identify other variables that may influence executive function among residents of coastal villages on Lombok Island. Methods: The study used a cross-sectional design with consecutive sampling. Data on sociodemographic characteristics, hypertension, diabetes mellitus, smoking status, and physical activity were collected. Statistical analyses employed Spearman's rank correlation test, Fisher's exact test, and logistic regression test. Results: A total of 39 participants were included, with an average age of 53.38 years. Most participants were female, had a low educational level, did not have hypertension or diabetes mellitus, had high physical activity levels, and were non-smokers. The average NRF2 level was 0.54 ng/mL. The correlation test showed no significant relationship between serum NRF2 levels and executive function. Fisher's exact test showed a significant relationship between gender and education with executive function. Furthermore, logistic regression analysis identified education level as a predictor of executive dysfunction. Conclusion: Serum NRF2 levels were not correlated with executive dysfunction. Educational level was identified as a predictive factor for executive dysfunction.